Transformative policy mixes in socio-technical scenarios: The case of the low-carbon transition of the German electricity system (2010-2050) - Karoline S. Rogge; Benjamin Pfluger; Frank Geels (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
Global climate change represents one of the grand societal challenges which policy makers around the world have agreed to jointly tackle it under the Paris Agreement. Henceforth, much research and policy advice has focused on de-veloping model-based scenarios to identify pathways towards achieving corre-sponding decarbonisation targets. In this paper, we complement such model-based analysis (based on IMAGE and Enertile) with insights from socio-technical transition analysis (MLP) to develop socio-technical storylines that plausibly show how low-carbon transitions can be implemented. We take the example of the transition of the German electricity system towards renewable energies, and elaborate two transition pathways which are assumed to achieve an 80% reduction in GHG emissions by 2050, but differ in terms of lead actors, depth of change and scope of change: the first pathway captures the substitu-tion of technological components (pathway A) and assumes incumbents as lead actors and focuses on radical technological change while leaving other system elements intact; in contrast, pathway B (broader system transformation) postu-lates new entrants as lead actors, which rests on the assumption that trans-formative change occurs in the whole system, i.e. affecting the architecture of the system, technologies but also practises. For both pathways, we focus on how policy makers could govern such transition processes through transforma-tive policy mixes, and compare the requirements of such policy mixes depend-ing on the pathway pursued. We find that multi-dimensional socio-technical change going beyond technological substitution (pathway B) requires much greater emphasis on societal experimentation and a more proactive role for an-ticipatory deliberation processes from the outset. In contrast, shifting gear from a new entrant friendly past trajectory to an incumbent dominated pathway (pathway A) requires active agency from incumbents and is associated with what we have called regime stabilizing instruments which defend core principles of the old regime while simultaneously fulfilling decarbonisation as additional success criteria.
urn:nbn:de:0011-n-4617009
Keywords: 330; socio-technical scenarios; transformative policy mix; German Ener-giewende; MLP; energy system modelling; transition pathways